En enkätstudie av privata småskogsbrukares inställning till skogsbrukets certifiering - Dahlen, Erik (2014)
Moelven Skog AB is currently working actively to increase the number of certified forest owners in private small-scale forestry. This study was conducted in collaboration with Moelven Skog AB and seeks to learn why private small scale forest owners not yet have certified their forestry and what should be done to increase the number of certified forest owners. The study was conducted through a questionnaire study. The result of the study shows that information needs of forest certification to private small scale forest owners is great. Many non-certified forest owners have not even heard of either PEFC or FSC. The majority of respondents also have no education in forestry. Most of those surveyed stated that their main goal with their forest ownership is to keep well-managed forests. It was noted that the views and responses often differed among forest owners and could not be linked to any specific category of forest owners. One difference, however, that could be ascertained was that female forest owners in greater extent than male forest owners felt that the main goal of forestry is to increase/preserve nature values. Key findings in this study to increase the number of certified forest owners was that it is important to reach out with information but also to use well- reasoned arguments, depending on who the landowner is and what his/her goal is with their forestry. The certification benefits can be many for the forest owners and are meant to keep well-managed forests, good economy and preserve and enhance nature values in their forests.